Information Accessibility and Utilizatoin as Factors Influencing Decision-making of Managers in Commercial Banks in Nigeria - Popoola, S.O. (Ghana Library Journal, 2006)
This study investigated information accessibility and utilization as factors influencing decision-making of managers in commercial banks in Nigeria. Single stage random sampling with equal allocation method was used to select 550 managers from the 66 licensed commercial banks. The study revealed that there was a significant positive relationship between academic qualifications and information utilization in decision-making of the respondents (r = 0.88, P < 0.05). Information accessibility and utilization, when taken together significantly influenced decision-making of the respondents (F = 48.67, df = 2; 507, P < 0.05). Also, each of the two factors independently has a significant influence on decision-making of the respondents information accessibility (β = 0.6214; df = 507, T = 10.71, P < 0.05) and information utilization (β = 0.8246, df = 507, T = 12.49 P < 0.05). The study also found that information utilization has a greater relative influence than information accessibility on decision-making of the respondents. Information accessibility and utilization was found to have significant positive multiple relationship with decision-making of the respondents (R = 0.8428, P < 0.05). It is therefore recommended that the management should make relevant information accessible on time for the use of managers for improved decision-making in the Nigerian commercial banks.